Construction and development trends of intelligent mining basic platform - YU Yang; ZHANG Shen (Gong-kuang zidonghua, 2023)
Intelligent mines are the continuation of the development of digital mines and integrated automation systems. Compared to digital mines and integrated automation systems, intelligent mines have higher requirements for basic platforms. The basic platforms of intelligent mine are divided into two parts: network platform and data platform. The network platform is divided into backbone network and access network. The backbone network has gone through the development process of industrial bus network, 100 Mbit/s industrial Ethernet, 1000 Mbit/s industrial Ethernet, and 10 Gbit/s industrial Ethernet. This study analyzes the development process, advantages, disadvantages, and applicability of the backbone network from industrial bus to 10 Gbit/s industrial Ethernet. It is pointed out that industrial bus network and 100 Mbit/s industrial Ethernet are not suitable as intelligent mine backbone networks. The 1000 Mbit/s and 10 Gbit/s industrial Ethernet are currently the preferred backbone networks for intelligent mines. By analyzing the construction requirements of intelligent mine access networks, it is pointed out that the access networks of intelligent mines should have blind spot free access and underlying computing capabilities. Currently, wireless access networks are still difficult to possess these capabilities. Leakage communication system belongs to semi wireless mode, the application situation is limited, and the speed is not high. 5G is mainly a wireless transmission network with relatively flexible rate adaptability. It is suitable to be a pure access transmission network. Due to its lack of ad hoc network and underlying computing capabilities, it is limited in blind spot free monitoring applications. WSN has a certain degree of self-sufficient network and underlying computing capabilities. But its speed is relatively low. Especially when used in underground mines with multiple hops, the speed rate significantly decreases, and the power consumption increases, thereby reducing computing capabilities and self-organizing network capabilities. Therefore, new access network devices that meet the needs of intelligent mines need to be developed. The data platform approach based on discrete servers and simple virtual servers can no longer meet the requirements of intelligent mines for data platforms. This paper analyzes the architecture and key technologies of the data platform's hyperconverged service platform, the characteristics of hyperconverged services, and its adaptability to the construction of intelligent mines. It is pointed out that hyperconverged servers are the development direction of intelligent mine data platforms.